In vitro rumen fermentation, microbial protein synthesis and composition of microbial community of total mixed rations replacing maize silage with red clover silage. Issue 6 (11th August 2018) - Castro‐Montoya, Joaquín; Witzig, Maren; Rahman, Mizanur; Westreicher‐Kristen, Edwin; Dickhoefer, Uta
Abstract: This study aimed to evaluate in vitro fermentation characteristics, microbial protein synthesis and microbial community composition when replacing maize silage (MS) with red clover silage (RCS) in total mixed rations (TMR) of dairy cows. Treatments included TMR containing forage (MS and RCS) and concentrates (0.75:0.25) with targeted proportions (dry matter (DM) basis) of RCS in TMR of 0.15 (RCS15 ), 0.30 (RCS30 ), 0.45 (RCS45 ), and 0.60 (RCS60 ), in substitution of MS. Samples of the TMR were incubated using the in vitro Ankom RF technique with a mixture of rumen fluid and buffer solution (1:2 v/v) for 8 and 24 hr. Gas production and total short‐chain fatty acids concentration did not differ between diets, whereas ammonia‐nitrogen concentration increased with increasing level of RCS. Acetate proportion was not affected by RCS level, but propionate showed a linear increase with increasing level of RCS at the expenses of butyrate. Branched fatty acids proportions linearly declined, reflecting a reduced deamination of true protein. Gene copy numbers of protozoa linearly decreased with increasing RCS levels, while total numbers of bacteria and methanogens were not affected by diet. The amylolytic bacteria Ruminobacter amylophillus and Prevotella bryantii showed evidence to increase with higher RCS levels after 8 hr and 24 hr, respectively, whereas no effects of diet where observed for the fibrolytic bacteria Ruminococcus albus, Ruminococcus flavefaciens and Fibrobacter succinogenes . Concentrations of purine bases, and total N production in liquid‐associated microbes declined with increasing RCS levels, suggesting a negative impact of this feed on microbial growth. The findings of this study suggest that in general, microbial protein synthesis might be impaired by the substitution of MS by RCS, therefore caution should be taken when formulating diets for dairy cows using high levels of RCS as ingredient.